Bronsted Acid-Catalyzed Cyanotritylation of Aldehydes by Trityl Isocyanide - Cioc, Razvan C.; Schuckman, Peter; Preschel, Hans D.; Vlaar, Tjostil; Ruijter, Eelco; Orru, Romano V. A. (Organic letters, 2016)
Cyanohydrins are versatile intermediates toward valuable organic compounds like alpha-hydroxy carboxylic acids, alpha-amino aids, and beta-amino alcohols. Numerous protocols are available for synthesis of (O-protected) cyanohydrins, but all procedures invariably rely on the use of toxic cyanide sources. A novel cyanide-free synthesis of O-trityl protected cyanohydrins via a catalytic Passerini-type reaction involving aldehydes and trityl isocyanide is reported. The feasibility of a catalytic asymmetric reaction is demonstrated using chiral phosphoric acid catalysis.